HYGIENIC REQUIREMENTS FOR DRINKING WATER (Лучшие интеллектуальные исследования, 2025)
Abstract. The development of lower norms of mineralization due to the development of brine irrigation technology has become a period requirement, since the constant consumption of distilled or less mineralized water leads to a violation of the water-salt equality in the body, on the basis of which the osmoreceptive field reactions of the liver lie, as a result of which how much sodium is.